The effect of anxiety and depression on the risk of irritable bowel syndrome in migraine patients. (October 2017) - Wu, Mei-Fong; Yang, Yu-Wen; Chen, Yen-Yu
Highlights: Migraine is associated with an increased risk of developing IBS. The risk is most significant in patients without mood disorders. In patients with mood disorders, migraine does not additionally increase IBS risk. Abstract: Bidirectional co-morbidity between migraine and depression has been observed. Mood disorders are associated with an increased risk of both migraine and irritable bowel syndrome (IBS). The aim of this study was to evaluate the risk of developing IBS in patients with migraine and to compare the risks between those with and without anxiety or depression. This research used the data contained in the National Health Insurance Research Database (NHIRD). A total of 2859 subjects with migraine and 5718 age-, sex-, hypertension-, diabetes-, mood disorder-matched controls were identified. Both cohorts excluded subjects with pre-existing catastrophic illness and IBS diagnosed before the index visit or within 30 days after the index visit. All individuals of both cohorts were tracked until either having the diagnosis of IBS, loss of follow-up, or IBS free up to 7 years. During the 7-year follow-up period, 8.4% of patients with migraine and 5.4% of control cohort developed IBS. Migraine is associated with an increased risk of developing IBS (HR = 1.58, 95% CI: 1.33–1.87). When separating the cohort into those with mood disorder and without it, migraine is a significant risk factor of IBS in patients without mood disorders, but not in patients with co-existed mood disorders. The findings of this study suggest that migraine is a risk factor of future IBS development for those without comorbid anxiety or depression. However, migraine does not contribute significantly additional risk to IBS development in patients with comorbid anxiety or depression.